2006
DOI: 10.1038/sj.bjc.6603484
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of mammalian horizontal gene transfer by apoptotic DNA fragmentation

Abstract: Previously it was shown that horizontal DNA transfer between mammalian cells can occur through the uptake of apoptotic bodies, where genes from the apoptotic cells were transferred to neighbouring cells phagocytosing the apoptotic bodies. The regulation of this process is poorly understood. It was shown that the ability of cells as recipient of horizontally transferred DNA was enhanced by deficiency of p53 or p21. However, little is known with regard to the regulation of DNA from donor apoptotic cells. Here we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 18 publications
2
15
0
Order By: Relevance
“…ICAD expression and mutations were recently linked to some human cancers and to an animal model of skin cancer [20], [21], [32], [40], [41]. Along with these reports, our study strengthens the notion that DFF is an important factor in tissue homeostasis by participating in the maintenance of genomic stability.…”
Section: Discussionsupporting
confidence: 87%
“…ICAD expression and mutations were recently linked to some human cancers and to an animal model of skin cancer [20], [21], [32], [40], [41]. Along with these reports, our study strengthens the notion that DFF is an important factor in tissue homeostasis by participating in the maintenance of genomic stability.…”
Section: Discussionsupporting
confidence: 87%
“…Surprisingly, significant horizontal gene transfer occurs in DNase II null recipient cells even when the p53 pathway is functional. Furthermore, the frequency of horizontal gene transfer to p53 null recipient cells is reduced some 4-to 6-fold when DFF activation is inhibited in apoptotic donor cells [110].…”
Section: Dff In Horizontal Gene Transfermentioning
confidence: 99%
“…Several investigations have shown that this can occur when donor cell apoptotic bodies are engulfed by phagocytic recipient cells [108][109][110]. The process can have important consequences because dying tumor cells can transfer their oncogenes to recipient cells and lead to the spreading of malignant transformation [109,111].…”
Section: Dff In Horizontal Gene Transfermentioning
confidence: 99%
“…This process can be remarkably efficient [28], requires CAD [29], and may induce tumor formation in vivo , possibly through the induction of gene translocations [30]. The tumor suppressor gene p53 prevents cells from replicating the transferred DNA, providing a possible explanation for the ability of cells carrying a mutant p53 gene to acquire genetic alterations [15].…”
Section: Introductionmentioning
confidence: 99%